Star formation scaling relations at ∼100 pc from PHANGS: impact of completeness and spatial scale - Pessa, Ismael; Schinnerer, E.; Belfiore, F.; Emsellem, E.; Leroy, A. K.; Schruba, A.; Kruijssen, Diederik; Pan, H.-A.; Blanc, G. A.; Sanchez-Blazquez, P.; Bigiel, F.; Chevance, Mélanie; et al. (Astronomy and astrophysics, 2021)
Aims. The complexity of star formation at the physical scale of molecular clouds is not yet fully understood. We investigate the mechanisms regulating the formation of stars in different environments within nearby star-forming galaxies from the Physics at High Angular resolution in Nearby GalaxieS (PHANGS) sample. Methods. Integral field spectroscopic data and radio-interferometric observations of 18 galaxies were combined to explore the existence of the resolved star formation main sequence (Σstellar versus Σ SFR ), resolved Kennicutt-Schmidt relation (Σmol. gas versus ΣSFR), and resolved molecular gas main sequence (Σstellar versus Σmol. gas), and we derived their slope and scatter at spatial resolutions from 100 pc to 1 kpc (under various assumptions).Results. All three relations were recovered at the highest spatial resolution (100 pc). Furthermore, significant variations in these scaling relations were observed across different galactic environments. The exclusion of non-detections has a systematic impact on the inferred slope as a function of the spatial scale. Finally, the scatter of the Σmol. gas + stellar versus ΣSFR correlation is smaller than that of the resolved star formation main sequence, but higher than that found for the resolved Kennicutt-Schmidt relation. Conclusions. The resolved molecular gas main sequence has the tightest relation at a spatial scale of 100 pc (scatter of 0.34 dex), followed by the resolved Kennicutt-Schmidt relation (0.41 dex) and then the resolved star formation main sequence (0.51 dex). This is consistent with expectations from the timescales involved in the evolutionary cycle of molecular clouds. Surprisingly, the resolved Kennicutt-Schmidt relation shows the least variation across galaxies and environments, suggesting a tight link between molecular gas and subsequent star formation. The scatter of the three relations decreases at lower spatial resolutions, with the resolved Kennicutt-Schmidt relation being the tightest (0.27 dex) at a spatial scale of 1 kpc. Variation in the slope of the resolved star formation main sequence among galaxies is partially due to different detection fractions of ΣSFR with respect to Σstellar.